Electronic ballast for high pressure sodium lamps..assessment of appropriateness for Meralco's adoption - Siao, Feldimir D. (University of the Philippines Diliman, 2004)
High pressure sodium (HPS) lamps are widely recognized as the most efficient light source among high intensity discharge lamps. This type of lamp requires a regulating device known as ballast, similar to the typical household ballast for the fluorescent lamps. Also, HPS lamp requires a starting device known as an ignitor that is similar to fluorescent lamps' starter. Currently, MERALCO utilizes a reactor type ballast for these HPS lamps. Advancement in ballast technology has utilized electronic components as an alternative to magnetic type (core and coil) ballast. The most commonly use is the high frequency electronic ballast which offers several advantages over the conventional magnetic ballast such as the lower power consumption, more constant lamp output, lesser weight and decrease lamp flicker. The only major disadvantages of this electronic ballast would be its relatively higher cost and unproven reliability. Electronic ballast offers an opportunity for MERALCO to lower the cost of street lighting operation and maintenance due to its lower power consumption and increase lamp life. This assessment on the appropriateness of the electronic ballast technology aimed to explore the possibility in its application within MERALCO, other local utilities and government agencies involved in street lighting activities. Objectives of the assessment were to determine the feasibility of utilizing electronic ballast for high pressure sodium lamp as replacement to existing magnetic type ballast, identification of the areas for application of the electronic ballast and development of the material and equipment specification which includes the acceptance test procedures. Typically for the majority of MERALCO's high pressure sodium streetlight installation which is rated at 70 watts, a 7-watt reduction per luminaire in energy consumption can be realized. MERALCO could realize an annual energy savings of PHP168.43 per luminaire on the 2004 power purchase cost of PHP4.74 per kilowatt-hour or an overall savings of PHP42.1 million upon full implementation with the conversion of the remaining 125W mercury streetlight to HPS luminaires equipped with electronic ballast and gradual control gear replacement of the existing 70W HPS luminaires. Technology assessment framework was used to evaluate electronic ballast technology and its impact on economics, psychological, institutional, social, technical, legal and environmental aspects. Primary data gathering includes testing of the electronic ballast, confirmation of its usage by other ASEAN utilities and their experiences in the utilization of the electronic ballast, and consultation with Electrical Testing personnel. Secondary data gathering was obtained through library and internet research. The data analysis involved a technical evaluation of the electronic ballast in comparison to the existing magnetic type ballast and a cost-benefit analysis to assess its economic feasibility. A sensitivity analysis was done based on voltage fluctuation and energy purchase cost. This provided the recommendation for the utilization of electronic ballast for streetlights luminaires. The initial overall assessment in the appropriateness of the electronic ballast for HPS lamp showed that it is favorable for adoption with consideration of the technical advantages and reduction in the life cycle cost. The higher initial cost can be recovered in less than 4 years. However, reliability in less then 4 years. However, reliability is still major concern to be resolved through additional pilot installation of the product and continued inquiry of other possible suppliers such as the recent interest that Philip lighting has shown to provide samples of HPS electronic ballast.